Pelatihan Melalui Web Seminar Dampak UU HPP Terhadap Pelaku UMKM Di Era Pandemi - Ferry Irawan (PT WIM Solusi Prima, 2021)
The Law on Harmonization of Tax Regulations (UU HPP) has been effective since October 29, 2021. One of the objectives of the HPP Law is to increase the economic growth, including Micro, Small and Medium Enterprises (MSMEs). Community Service Activities through this web seminar (webinar) aim to provide an understanding of the HPP Law in relation with MSMEs. There are several procedures carried out in the implementation of this web seminar. First, the presentation of the speaker. Second, it was followed by a discussion either through the chat box or direct interaction. Based on the responses from the webinar participants, it can be seen that this activity adds to the understanding of the participants regarding the HPP Law and its relationship with MSMEs. Undang-Undang Harmonisasi Peraturan Perpajakan (UU HPP) telah diberlakukan sejak 29 Oktober 2021. Salah satu tujuan UU HPP adalah meningkatkan pertumbuhan ekonomi termasuk di dalamnya Usaha Mikro, Kecil dan Menengah (UMKM). Kegiatan Pengabdian kepada Masyarakat melalui web seminar (webinar) ini bertujuan untuk memberikan pemahaman atas UU HPP dalam kaitannya sebagai pendorong UMKM. Terdapat beberapa prosedur yang dilakukan dalam dalam pelaksanaan web seminar ini. Pertama, pemaparan dari narasumber. Kedua, dilanjutkan dengan diskusi baik melalui chat box maupun berinteraksi secara langsung. Berdasarkan respon dari peserta webinar, dapat diketahui bahwa kegiatan ini menambah pemahaman para peserta terkait UU HPP dan hubungannya dengan UMKM.